2020
DOI: 10.1039/c9cc08361h
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated carboxylic acids as powerful building blocks for the formation of bimolecular monolayers

Abstract: Fluorination transforms a simple carboxylic acid into a highly effective building block for the formation of bimolecular monolayers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
(46 reference statements)
1
5
0
Order By: Relevance
“…These two planar molecules are structural isomers differing in the positions of their pyridyl nitrogen atoms. The nitrogen atoms within such pyridyl groups have previously been shown to be effective halogen bond acceptor sites in networks formed under similar conditions to those used in this study. Furthermore, we have previously demonstrated that 3TPTZ and 4TPTZ interact very favorably with fluorinated carboxylic acids, like 4BTFBA, via strong O–H···N­(pyridyl) interactions . It should also be noted that despite their different structures, from an electrostatic perspective, the ability of the N­(pyridyl) sites of 3TPTZ and 4TPTZ to act as halogen/hydrogen bond acceptors is essentially the same (see the Supporting Information, section 3).…”
Section: Resultssupporting
confidence: 59%
“…These two planar molecules are structural isomers differing in the positions of their pyridyl nitrogen atoms. The nitrogen atoms within such pyridyl groups have previously been shown to be effective halogen bond acceptor sites in networks formed under similar conditions to those used in this study. Furthermore, we have previously demonstrated that 3TPTZ and 4TPTZ interact very favorably with fluorinated carboxylic acids, like 4BTFBA, via strong O–H···N­(pyridyl) interactions . It should also be noted that despite their different structures, from an electrostatic perspective, the ability of the N­(pyridyl) sites of 3TPTZ and 4TPTZ to act as halogen/hydrogen bond acceptors is essentially the same (see the Supporting Information, section 3).…”
Section: Resultssupporting
confidence: 59%
“…Fluorinated carboxylic acids are an important structural component widely found in pharmaceuticals and bioactive compounds, 51 but the defluorinative electrocarboxylation of fluoroalkenes has rarely been reported due to the thermodynamic and kinetic stability of C–F bonds. In 2020, Zhou and colleagues disclosed a facile and economical direct defluorinative carboxylation of gem -difluoroalkenes with CO 2 , in an undivided cell equipped with a Pt plate as a cathode and nickel as an anode at room temperature at a constant current of 8.0 mA cm −2 with 6.7 F mol −1 (Scheme 25).…”
Section: Direct Electroreductionmentioning
confidence: 99%
“…Medicinal chemists who are making oxygen to fluorine bioisosteric replacements need to understand the effects this replacement will have on the physicochemical properties of a molecule, particularly lipophilicity because of the key role it plays in biodistribution, metabolism, and binding. As part of our interest in the chemistry of fluorinated aromatic compounds, in this paper, we will describe how structural features in a drug-like molecule may affect the change in lipophilicity on transformation of an aromatic hydroxy or methoxy group to a fluorine atom.…”
Section: Introductionmentioning
confidence: 99%